2016
DOI: 10.3732/ajb.1500214
|View full text |Cite
|
Sign up to set email alerts
|

Pollen limitation is not the rule in nival plants: A study from the European Central Alps

Abstract: Our results do not support the idea of chronic, widespread pollen limitation in the subnival but rather fit into the concept of parental optimism by overinvesting in the number of ovules as an adaptation to variable resource availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…Although studies examining pollen limitation in natural plant populations are largely focused on pollination quantity, qualitative pollen limitation has been repeatedly highlighted as a critical factor limiting reproductive success (Aizen & Harder, ; Alonso, Herrera, & Ashman, ; Ashman & Morgan, ). In this regard, recent investigations are providing empirical support for the important role of pollen quality (Castilla, Alonso, & Herrera, ; Vaughton & Ramsey, ; Wagner, Lechleitner, & Hosp, ). Our results suggest that stigmas of P. bourgaeana flowers are receiving a substantial amount of either self‐ or genetically related pollen, which is qualitatively limiting their seed production.…”
Section: Discussionmentioning
confidence: 95%
“…Although studies examining pollen limitation in natural plant populations are largely focused on pollination quantity, qualitative pollen limitation has been repeatedly highlighted as a critical factor limiting reproductive success (Aizen & Harder, ; Alonso, Herrera, & Ashman, ; Ashman & Morgan, ). In this regard, recent investigations are providing empirical support for the important role of pollen quality (Castilla, Alonso, & Herrera, ; Vaughton & Ramsey, ; Wagner, Lechleitner, & Hosp, ). Our results suggest that stigmas of P. bourgaeana flowers are receiving a substantial amount of either self‐ or genetically related pollen, which is qualitatively limiting their seed production.…”
Section: Discussionmentioning
confidence: 95%
“…In some alpine species, flower longevity compensation seems to work quite well (Bingham & Orthner, 1998;Pickering, 1997), but in others, as in the Andes, it is not fail-safe (e.g., Wu et al, 2015). Insects appear to be sufficiently abundant to enable good seed set on some high nival species in the European Alps (Wagner et al, 2016). Nevertheless, it would not be surprisingly that the abundant visitation recorded in this study is recent and due to global warming which is strongly elevation-dependent (Falvey & Garreaud, 2009;Gobiet et al, 2014;Pepin et al, 2015) and is occurring at a faster rate in the northern hemisphere (Friedman, Hwang, Chiang, & Frierson, 2013).…”
Section: R P Y G G a M S P M A D S A T H Y P T H R N A S Co M Chu Oppmentioning
confidence: 99%
“…Alpine areas and the Arctic thus are prime candidates for ovule bet-hedging (Burd et al, 2009). However, although the possibility of ovule oversupply has been mentioned by some authors (Fulkerson et al, 2012;Wagner, Lechleitner, & Hosp, 2016), no study has explicitly tested the ovule bet-hedging hypothesis in these harsh environments for animal pollinators.…”
Section: Introductionmentioning
confidence: 99%
“…Altitudinal scale investigation can be a good proxy for inferring the impact of temperature change on pollinator assemblage and activity as temperature varies with elevation (Hegland et al 2009). Many researchers have reported that pollinator assemblages tend to change from bees at lower altitudes (Totland 1993;Hoiss et al 2012;Zhao and Wang 2015) to flies at higher altitudes (Arroyo et al 1982;Totland 1993;Lázaro et al 2008;Inouye et al 2015;Wagner et al 2016) and that their activity decreases with elevation (Arroyo et al 1985;Primack and Inouye 1993;Bingham and Orthner 1998;Zhao and Wang 2015). However, relatively few studies have focused on how temperature changes during a flowering season affect high-altitude plant-pollinator assemblage and activity (Primack 1978;Mizunaga and Kudo 2017).…”
Section: Introductionmentioning
confidence: 99%